2019
DOI: 10.1097/fbp.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monoamine uptake inhibitors on pain-related depression of nesting in mice

Abstract: Pain is a significant public health problem, and assessment of pain-related impairment of behavior is a key clinical indicator and treatment target. Similar to opioids and NSAIDs, dopamine (DA) transporter inhibitors block pain-related depression of intracranial self-stimulation (ICSS) in rats. The primary goal of the present study was to determine if the effects of monoamine uptake inhibitors on pain-related depression of ICSS in rats extend to an assay of pain-related depression of nesting in mice. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In the current study we used two established analgesics to assess the validity of this procedure. Consistent with previous studies using a variety of assays of pain stimulated behavior (13,17,26,36), we found that the NSAID ketoprofen dose-dependently blocked pain-related depression of shredding. Moreover, the present study showed that ketoprofen's effects were selective for blocking pain-related depression by intraperitoneal injection of lactic acid, and did not impact depression of behavior by a pharmacological stimulus, the kappa opioid agonist U69,593.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study we used two established analgesics to assess the validity of this procedure. Consistent with previous studies using a variety of assays of pain stimulated behavior (13,17,26,36), we found that the NSAID ketoprofen dose-dependently blocked pain-related depression of shredding. Moreover, the present study showed that ketoprofen's effects were selective for blocking pain-related depression by intraperitoneal injection of lactic acid, and did not impact depression of behavior by a pharmacological stimulus, the kappa opioid agonist U69,593.…”
Section: Discussionsupporting
confidence: 91%
“…Examples of this approach include pain-related depression of feeding (23,26), wheel-running (9, 10, 12, 29, 30), burrowing (11,(31)(32)(33)(34) and nesting. Some previous studies have used rating systems to indicate nest quality (32), but recent studies use variations of a general approach that involves assessment of the collection and consolidation of nesting material within the home cage which potentially allows for more objective measurement of the dependent variable (13)(14)(15)(16)(17)(18)(19)35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations